PAM-50 predicts local recurrence after breast cancer surgery in postmenopausal patients with ER+/HER2– disease: results from 1204 patients in the randomized ABCSG-8 trial. Issue 3 (20th February 2021) - Fitzal, F; Filipits, M; Fesl, C; Rudas, M; Greil, R; Balic, M; Moinfar, F; Herz, W; Dubsky, P; Bartsch, R; Ferree, S; Schaper, C; et al.
Abstract: Background: The aim of this study was to investigate whether the PAM-50-based 46-gene assay carries prognostic value for risk of local recurrence of breast cancer. Methods: The Austrian Breast and Colorectal Cancer Study Group (ABCSG) 8 RCT compared 5 years of tamoxifen with tamoxifen for 2 years followed by anastrozole for 3 years in postmenopausal women with endocrine receptor-positive breast cancer. This study included patients from the trial who had breast-conserving surgery for whom tumour blocks were available for PAM-50 analysis. Results: Tumour blocks from 1204 patients who had breast-conserving surgery were available for the PAM-50 analysis, and 1034 of these received radiotherapy. After a median follow-up of 10.8 years, 23 local events had been observed, corresponding to an overall local recurrence risk of 2.2 per cent. Univariable competing-risk analysis demonstrated that patients at low risk according to PAM-50 analysis (risk-of-recurrence (ROR) score less than 57) had a significantly lower incidence of local recurrence than those in the high-risk group at 5 years (0.1 (95 per cent c.i. 0 to 0.7) versus 2.2 (0.9 to 4.6) per cent respectively; subhazard ratio (SHR) 17.18, 95 per cent c.i. 2.06 to 142.88; P = 0.009) and 10 years (0.9 (0.4 to 2.0) versus 3.8 (1.9 to 6.6) per cent; SHR 4.76, 1.72 to 13.17; P = 0.003). Multivariable analyses that included ROR score, age, tumour size, nodal status, type of surgery, tumor grade, and trial-specific endocrine therapy confirmed that ROR score was an independent prognostic factor for risk of local recurrence. Analysis of the women randomized to radiotherapy or control after breast conservation showed that PAM-50 was not predictive of radiotherapy effect. Conclusion: PAM-50 can be used as a prognostic tool for local recurrence risk in postmenopausal women with hormone receptor-positive breast cancer treated with endocrine therapy. The test was not predictive for the benefit of radiotherapy. Abstract : Predicting local recurrence risk after early breast cancer treatment has important implications for decision-making regarding local therapy. The aim of this study was to investigate whether a PAM-50-based risk-of-recurrence score adds additional prognostic value to known clinical risk factors for local recurrence risk in early-stage breast cancer, and to evaluate its predictive role regarding radiotherapy benefit. It was demonstrated that a PAM-50-based assay can be used as a prognostic tool for local recurrence risk in postmenopausal women with hormone receptor-positive breast cancer treated with endocrine therapy and who had received standard-of-care local therapy. Predictive value for the benefit of radiotherapy was not shown. Predicting local recurrence (LR)-risk after early breast cancer treatment has important implications for local therapy decision making. The aim of this study was to investigate whether a PAM-50-based assay (Prosigna, NanoString Technologies) risk of recurrence (ROR) score adds additional prognostic value to known clinical risk-factors for LR risk in early stage breast cancer, and to evaluate its predictive role regarding radiotherapy benefit. We accomplished demonstrating that a PAM-50-based assay can be used as a prognostic tool for LR risk in postmenopausal hormone-receptor positive endocrine-treated breast cancer patients who have received standard of care local therapy. A predictive value for radiotherapy benefit was not shown. Finds ultra low-risk patients